Ukrainian economy development trends estimation based on the analysis of structural shifts - Serhieieva, L.; Us, G.; Chudaieva, I.; Makarenko, O.; Сергєєва, Людмила Нільсівна (My University, 2019)
Abstract. The article elaborates upon development trends in the economy of Ukraine taking into account structural shifts. Herewith it is proposed a stagewise procedure for the analysis of development trends of the country’s economy taking into account structural changes in industry and employment by sectors of economic activity. The authors present an indicator of structural shifts and evaluate efficiency of structural changes in the Ukrainian economy. In general, the structural shifts efficiency estimation shows that they are not effective in the Ukrainian economy, as the share of the services sector is increasing, while the productivity is growing more rapidly in the industry. The use of the presented analysis procedure will allow enhance efficiency of the strategies formulation of the country’s economic development.